2002
DOI: 10.1108/03090590210444955
|View full text |Cite
|
Sign up to set email alerts
|

Critical reflective working behaviour: a survey research

Abstract: In this paper critical reflective working behaviour will be operationalized. Second, the question will be raised which factors have impact on critical reflective working behaviour. The following dimensions of critical reflective working emerge: reflection, vision sharing, challenging groupthink, asking for feedback, experimentation and awareness of employability. In a survey amongst 742 respondents these dimensions are validated. Important influencing factors seem to be selfcfficacy and participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 6 publications
5
85
0
7
Order By: Relevance
“…Several qualitative studies, discussed in the Literature Review, have also shown a positive relationship between these two constructs (e.g., Milner & Woolfolk Hoy, 2003;Stallions, Murrill, and Earp, 2012;Runhaar et al, 2010;Thoonen et al, 2011;Woerkom, Nijhof, & Nieuwenhuis, 2002;Yeh, 2006). The small effect size of their correlation in our study can be explained in terms of Wheatley's (2002) argument that adopting a reflective approach to teaching and therefore questioning one's own teaching approach and style entails a healthy dose of efficacy doubt, as low perceived efficacy can encourage teachers to reflect on and improve their teaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several qualitative studies, discussed in the Literature Review, have also shown a positive relationship between these two constructs (e.g., Milner & Woolfolk Hoy, 2003;Stallions, Murrill, and Earp, 2012;Runhaar et al, 2010;Thoonen et al, 2011;Woerkom, Nijhof, & Nieuwenhuis, 2002;Yeh, 2006). The small effect size of their correlation in our study can be explained in terms of Wheatley's (2002) argument that adopting a reflective approach to teaching and therefore questioning one's own teaching approach and style entails a healthy dose of efficacy doubt, as low perceived efficacy can encourage teachers to reflect on and improve their teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Kitsantas and Baylor (2001), for example, found that self-reflection about instructional planning encouraged learners to reconsider their self-efficacy beliefs and develop a more realistic understanding of their planning abilities. In the context of industry, selfefficacy was found to be the most important predictor of employees' critical reflective working behaviour, such as challenging group-think and experimentation (van Woerkom, Nijhof & Nieuwenhuis, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A reflexão crítica, em particular, tem sido percebida como um mecanismo de grande potencial se empregada no nível do grupo e da organização, já que possibilita a revisão de pressupostos organizacionais (DENSTEN;GRAY, 2001;WOERKOM;NIJHOF;NIEUWENHUIS, 2002;HOYRUP, 2004 …”
Section: Reflexão: Do Nível Individual Para O Nível Organizacionalunclassified
“…While some relevant theory may be best learned in a classroom environment, workplaces are often necessary to bring that theory to life. Other research has shown that it is easier to develop professional skills in work-based training than transferring theoretical knowledge, learned at school, into practice (Aarkrog, 2005;Woerkom, Nijhof and Nieuwenhuis, 2002). Section 2.3 below argues that part of the payoff from stronger links between the VET system and employers should be an expansion of good quality workplace training in Chile.…”
Section: Using Workplace Training To Develop Soft General Skillsmentioning
confidence: 99%